The Phenomenon of the Interpersonal Encounter in Antoni Kępiński’s Philosophical Thought - Antoszewska, Anna (Folia Philosophica, 2021)
In her article, Anna Antoszewska discusses the phenomenon of the interpersonal encounter in the philosophical thought of professor Antoni Kępiński, the author of Psychopatie, among other books. She lays special emphasis on the sources of his philosophical insights. While there is no doubt as to the originality of these insights, getting acquainted with numerous interpretations of Kępiński’s philosophical thought makes a researcher aware of the difficulty of unambiguously identifying the position of this outstanding psychiatrist and founder of axiological psychiatry. Polish scholars interested in Kępiński’s views remain sensitive to the contradictions among the concepts he uses in his philosophical reflections.